Assessment of heavy metals contamination and its effects on oyster (Saccostrea cucullata) biometry parameters in the Asaluyeh port coasts, Persian Gulf, Iran. Issue 6 (2nd November 2017) - Delshab, Hossein; Farshchi, Parvin; Mohammadi, Mehdi; Moattar, Faramarz
Abstract: The current study examines biometric parameters and concentration of some heavy metals in soft tissues of Saccostrea cucullata in the Asaluyeh coast, Persian Gulf, Iran. The metals concentration in the soft tissue of the Saccostrea cucullata ranged as: Zn: 765–3411 mg kg −1, Cu: 120.3–580.6 mg kg −1, Cd: 0.13–3.5 mg kg −1, As: 0.39–3.3 mg kg −1, Pb: 0.05–1.64 mg kg −1, Ni: 0.02–0.44 mg kg −1, V: 0.06–0.32 mg kg −1, Cr: 0.02–0.16 mg kg −1 and Hg: 0.002–0.068 mg kg −1 . The results showed that the concentration of total heavy metals in oysters of the control station (CA) is usually lower. The results also indicated lack of correlation between oyster biometric parameters and bioaccumulated heavy metals, except between Cu and longitudinal diameter ( R  = 0.77). The concentration of heavy metals is higher than limits recommended by the World Health Organization, except for Cd and Pb.